Dermal penetration of 2-phenoxyethanol in humans: in vivo metabolism and toxicokinetics - Eckert, Elisabeth; Jäger, Thomas; Leibold, Edgar; Bader, Michael; Göen, Thomas; Hiller, Julia (Archives of Toxicology, 2024)
2-Phenoxyethanol (PhE) is an amphiphilic organic compound frequently used as a broad-spectrum preservative in cosmetic products and other consumer goods. PhE is also used as a biocidal component in occupational settings. A previous volunteer study by our working group following oral exposure to PhE showed that PhE is almost completely taken up into the human body followed by an extensive metabolization and fast urinary elimination. However, with respect to the importance of transdermal uptake, we now conducted another volunteer study applying dermal PhE exposure: five volunteers were dermally exposed with 0.4 mg/kg body weight of PhE each on a specified 800 cm2 skin area using non-occlusive conditions. Subsequently, blood and urine samples were collected up to 48 h post-exposure. The present study illustrates the fast transdermal uptake of PhE. Following systemic resorption, PhE was extensively metabolized and rapidly eliminated in urine mainly in form of the metabolites PhAA (phenoxyacetic acid) and 4-OH-PhAA (4-hydroxyphenoxyacetic acid) accounting together for over 99% of the renally excreted PhE dose. The absolute urinary recovery rate of PhE was observed to be significantly lower following dermal exposure compared to oral uptake indicating a dermal resorption rate of PhE of about 45% in humans. The present study provides for the first time detailed insights into human biotransformation and toxicokinetics of PhE after dermal exposure, thus establishing a reliable strategy for human biomonitoring of PhE. The here presented results may thus be useful for further toxicokinetic modeling and forward dosimetry.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 2-Phenoxyethanol; Biomonitoring; Ethylene glycol monophenyl ether; Phenoxyacetic acid; Skin penetration; Urine